Dopamine Receptor and Hypertension - Zeng, Chunyu; Eisner, Gilbert M.; Felder, Robin A.; Jose, Pedro A. (Current Medicinal Chemistry - Cardiovascular & Hematological Agents, 2005)
Dopamine plays an important role in the pathogenesis of hypertension by regulating epithelial sodium transport and reactive oxygen and by interacting with vasopressin, renin-angiotensin, and the sympathetic nervous system. Decreased renal dopamine production and / or impaired dopamine receptor function have been reported in hypertension. Disruption of any of the dopamine receptors (D1, D2, D3, D4, and D5) results in hypertension. In this paper, we review the mechanisms by which hypertension develops when dopamine receptor function is perturbed.
Keywords: endocytosis